PENGGUNAAN JENAZAH UNTUK KEPENTINGAN PENELITIAN ILMIAH PERSPEKTIF FAZLUR RAHMAN - Abdurahman Syayuthi (Program Pascasarjana UIN Sumatera Utara, 2020)
Abstract: The development of science and technology that is currently going on in the field of medical transplant surgery or the use of dead bodies for the purposes of scientific research. In this case the use of dead bodies that was one of the findings of the modern medical technology with the methods in the form of tissue or organs removal of the body from one place to another to replace organs that are not healthy and not functioning properly. It means that this technological advancement in the field of medical studies helps many parties, but the attempt to use of dead bodies in this study also clearly raises several problems that have an impact on morality. This study aimed to find out how the concept of Fazlur Rahman’s methodology and how the law views about the use of dead bodies for scientific research. This study used methodology of normative juridical approaches that are directly related to library research and qualitative method gathered data collection from primary, secondary legal sources, and documents. The results of this study mentioned that Fazlur Rahman's methodology using the